2019
DOI: 10.3389/fnins.2019.00379
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Direct Current Neural Modulation: Theory, Feasibility, and Efficacy

Abstract: Implantable neuroprostheses such as cochlear implants, deep brain stimulators, spinal cord stimulators, and retinal implants use charge-balanced alternating current (AC) pulses to recover delivered charge and thus mitigate toxicity from electrochemical reactions occurring at the metal-tissue interface. At low pulse rates, these short duration pulses have the effect of evoking spikes in neural tissue in a phase-locked fashion. When the therapeutic goal is to suppress neural activity, implants typically work ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 175 publications
(285 reference statements)
1
29
0
Order By: Relevance
“…iDC stimulation effects via efferent fibers therefore also have to be considered. This highlights the need to understand the effect of electrical stimulation beyond the primary neural target, particularly with stimulation methodologies like DC that may not follow assumptions about neural responses that are based on pulsed stimulation 12 . One resource that may be useful for continued investigation of iDC stimulation effects are the detailed models of field strength and neural effect that have been developed for tDCS experiments in the cortex 16,25,34–36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…iDC stimulation effects via efferent fibers therefore also have to be considered. This highlights the need to understand the effect of electrical stimulation beyond the primary neural target, particularly with stimulation methodologies like DC that may not follow assumptions about neural responses that are based on pulsed stimulation 12 . One resource that may be useful for continued investigation of iDC stimulation effects are the detailed models of field strength and neural effect that have been developed for tDCS experiments in the cortex 16,25,34–36 .…”
Section: Discussionmentioning
confidence: 99%
“…An evolution of this concept is the focused, safe delivery of ionic direct current (iDC) separately into each vestibular semicircular canal through an electrolyte-filled microcatheter with the intent to restore functional vestibular sensation for patients suffering from bilateral vestibular dysfunction 911 . iDC has an advantage over traditional pulse-based neuro-stimulation, in that iDC can excite or inhibit the vestibular system depending on the polarity of the stimulating current 12 . This is important because information about the direction and magnitude of head rotation is encoded in the vestibular afferents as either an increase or decrease around a spontaneous firing rate 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to conventional pulsatile neural prostheses used to excite neural targets ( Loeb, 2018 ), direct current (DC) neuromodulation emerged as having potential for use in a variety of new medical treatments due to its unique ability to evoke a broad range of beneficial clinical effects on target neurons ( Aplin and Fridman, 2019 ). These have been shown in its ability to achieve peripheral nerve block for pain suppression ( Bhadra and Kilgore, 2004 ; Yang et al., 2018 ), modulate cortical activity and synaptic connectivity for psychiatric treatments ( Bikson et al., 2004 ; Radman et al., 2007 ; Brunoni et al., 2012 ), and excite and inhibit vestibular afferent activity to treat balance disorders ( Manca et al., 2019 ; Aplin et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These have been shown in its ability to achieve peripheral nerve block for pain suppression ( Bhadra and Kilgore, 2004 ; Yang et al., 2018 ), modulate cortical activity and synaptic connectivity for psychiatric treatments ( Bikson et al., 2004 ; Radman et al., 2007 ; Brunoni et al., 2012 ), and excite and inhibit vestibular afferent activity to treat balance disorders ( Manca et al., 2019 ; Aplin et al., 2020 ). Recent innovations with DC stimulation technology have also led to the development of safe direct current stimulation (SDCS) ( Fridman and Della Santina, 2013 ; Cheng et al., 2017 ; Fridman, 2017 ; Ou and Fridman, 2017 ; Aplin and Fridman, 2019 ), which makes it possible to chronically deliver localized direct ionic current from an implantable device. Preliminary behavioral testing of the SDCS for vestibular balance disorders as well as for the treatment of pain suppression revealed that DC neuromodulation has multiple beneficial effects on targeted neural populations that cannot be produced with pulsatile stimulation, including inhibiting, exciting, and sensitizing neural targets in a natural, desynchronized manner ( Yang et al., 2018 ; Aplin and Fridman, 2019 ; Aplin et al., 2019a , 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…Some research in the cochlear implant space has investigated the “steering” of stimulation currents in order to achieve higher precision (Berenstein et al, 2008 ). Safe direct current stimulation has also been explored as a possible method for selectively exciting and inhibiting neurons (Fridman & Della Santina, 2013 ; Aplin & Fridman, 2019 ). It is not yet known how these different types of stimulation might affect somatosensory perception.…”
Section: Discussion: From Type 1 To Typementioning
confidence: 99%